2016
DOI: 10.1007/s11307-016-0955-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Radiation Dosimetry of [18F]Mefway in Humans

Abstract: For a typical single injection of 185 MBq (5 mCi), the dose will result in 87.1 mSv for the urinary bladder wall. To reduce radiation burden, the bladder voiding can be used before [F]Mefway PET scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other human PET studies suggested an estimated effective dose of 40.23 μSv/MBq 137 and optimal imaging timing of 60−80 min 138 for [ 18 F]trans-27, and this radioligand was demonstrated to metabolize through the gastrourinary tract. 137 In a recent PET study with major depressive episode patients, 139 [ 18 F]trans-27 could efficiently evaluate the 5-HT 1A receptor density but failed to discriminate the therapeutic response. As a result, [ 18 F]trans-27 exhibited great potential in clinical PET studies of neurologic and psychiatric disorders that affect the mesial temporal lobe.…”
Section: Pet Ligands For 5-ht 1a Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other human PET studies suggested an estimated effective dose of 40.23 μSv/MBq 137 and optimal imaging timing of 60−80 min 138 for [ 18 F]trans-27, and this radioligand was demonstrated to metabolize through the gastrourinary tract. 137 In a recent PET study with major depressive episode patients, 139 [ 18 F]trans-27 could efficiently evaluate the 5-HT 1A receptor density but failed to discriminate the therapeutic response. As a result, [ 18 F]trans-27 exhibited great potential in clinical PET studies of neurologic and psychiatric disorders that affect the mesial temporal lobe.…”
Section: Pet Ligands For 5-ht 1a Receptorsmentioning
confidence: 99%
“…Fortunately, no accumulation of the radioactivity was observed in the bone (no substantial in vivo defluorination). Other human PET studies suggested an estimated effective dose of 40.23 μSv/MBq and optimal imaging timing of 60–80 min for [ 18 F] trans - 27 , and this radioligand was demonstrated to metabolize through the gastrourinary tract . In a recent PET study with major depressive episode patients, [ 18 F] trans - 27 could efficiently evaluate the 5-HT 1A receptor density but failed to discriminate the therapeutic response.…”
Section: Pet Ligands For 5-ht1a Receptorsmentioning
confidence: 99%